To determine the inverse function, we will write the function and reach the inversion by performing the required calculation, as follows:
![\begin{gathered} y=(x+3)/(x+7)\Rightarrow y(x+7)=x+3 \\ y\cdot x+7y=x+3\Rightarrow x\cdot y-x=3-7y \\ x(y-1)=3-7y \\ \\ x=(3-7y)/(y-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5l711txd57a0gjsezk0mufc9nz7xm2gul4.png)
From the solution developed above, we are able to conclude that the solution for the present question is the following:
![f^(-1)(x)=(3-7x)/(x-1)](https://img.qammunity.org/2023/formulas/mathematics/college/nc050311d6lort13eelo0saydte0uy8lfj.png)
Where the numerator is: 3 - 7x
Ans the denominator is: x - 1